MICROLEARNING IN UPC - Watson, Rachel (2007)
This work reflects upon the use of the 'microlearning' technique in the teacher'slearning proccess. The experience of microlearning in UPC is developed as part of the proccess of induction that 'Quality Education Department' (Departamento de Calidad Educativa) gives to the new teachers. The results of the term 2006-02 of the analysis of the 'teachers skills' in the microlearning are shown and the possibilities that this technique offers are disscussed. This helps the new teachers to reinforce their pedagogical skills and to understand and work under the Educational Model of the UPC. At the same time it gives and accepts feedback so that the teacher can continue to complement their pedagogical learning.